Transcriptome-based identification of PDGFA as a candidate secreted biomarker for hepatocellular carcinoma - Chesnokov, M.S.; Krivtsova, O.M.; Skovorodnikova, P.A.; Makarova, A.S.; Kustova, I.F.; Logacheva, M.D.; Penin, A.A.; Klepikova, A.V.; Shavochkina, D.A.; Kudashkin, N.E.; Moroz, E.A.; Patyutko, Y.I.; et al. (Вiopolymers and Cell, 2016)
Aim. Identification of candidate secreted biomarkers for hepatocellular carcinoma (HCC) diagnosis. Methods. Genes upregulated in HCC tissue and encoding secreted proteins were identified by RNA-seq. Gene expression changes in HCC were evaluated by RT-qPCR and meta-analysis of public databases. Biomarker properties were studied using ROC-curves, correlation and survival analysis. Results. PDGFA was identified by RNA-seq as an overexpressed gene encoding for a secreted protein in 5 HCC cases. PDGFA and GPC3 up-regulation was revealed in 17 of 19 HCC samples and in most cases from the public databases. Combination of PDGFA and GPC3 discerned HCC and non-tumor tissue better than PDGFA or GPC3 alone. PDGFA overexpression was associated with better overall survival of the patients at early HCC stage and with weaker tumor invasion into blood vessels. Conclusion. PDGFA is a valuable secreted biomarker for HCC that might be used in combination with GPC3 to increase its sensitivity. Мета. Ідентифкація потенційних біомаркерів, що секретується для діагностики гепатоцелюлярної карциноми (ГК). Методи. Гени, експресія яких підвищена в тканині ГК і які кодують білки, що секретуються, виявляли РНК-секвенуванням. Експресію генів оцінювали ЗТ-ПЛР або використовували інформацію з відкритих баз даних. Біомаркерні властивості оцінювали за допомогою ROC-кривих, аналізу кореляцій і виживання. Результати. РНК-секвенування п’яти випадків ГК виявило гіперекспресію PDGFA, що кодує секретуємий білок. Підвищення експресії PDGFA та GPC3 виявлено в 17 з 19 зразків ГК та для більшого випадку зразків у базах даних. Спільне використання PDGFA та GPC3 дозволяє точніше відрізнити ГК від непухлинної тканини печінки , ніж PDGFA або GPC3 окремо. Гіперекспресія PDGFA асоційована з кращим прогнозом для пацієнтів з ранніми стадіями ГК і низькою інвазією пухлини в судини. Висновки. PDGFA – перспективний біомаркер ГК, що секретується, який може бути використаний разом з GPC3 для підвищення його чутливості. Цель. Поиск потенциальных секретируемых биомаркеров для диагностики гепатоцеллюлярной карциномы (ГК). Методы. Гены, экспрессия которых повышена в ткани ГК и кодирующие секретируемые белки, выявляли РНК-секвенированием. Экспрессию генов оценивали ОТ-ПЦР или использовали информацию из открытых баз данных. Биомаркерные свойства оценивали с помо-щью ROC-кривых, анализа корреляций и выживаемости. Результаты. РНК-секвенирование 5 случаев ГК выявило гиперэкспрес-сию PDGFA, кодирующего секретируемый белок. Повышение экспрессии PDGFA и GPC3 выявлено в 17 из 19 образцов ГК и в большинстве случаев из баз данных. Совместное использование двух маркерных генов PDGFA и GPC3 позволяет дифференци-ровать ткань ГК от неопухолевой ткани печени лучше, чем PDGFA или GPC3 по отдельности. Гиперэкспрессия PDGFA ассо-циирована с лучшим прогнозом для пациентов с ранними стадиями ГК и низкой инвазией опухоли в сосуды. Выводы. PDGFA – перспективный секретируемый биомаркер ГК, который может быть использован вместе с GPC3 для повышения его чувстви-тельности.